2009
DOI: 10.1016/j.cyto.2009.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Human cancer cells have specifically lost the ability to induce the synergistic state caused by tumor necrosis factor plus interferon-β

Abstract: Tumor necrosis factor (TNF) and the members of the interferon (IFN) family are major inducible cytokines that function to counteract viral infections or cellular transformation. Recently, our lab has characterized a novel antiviral state which is induced in primary human fibroblasts by co-treatment with TNF plus IFNβ. Here, we demonstrate that this synergistic state is both antiviral and cytostatic for primary human cells. Significantly, we observed that a wide spectrum of transformed human cancer cells have u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 13 publications
1
57
0
Order By: Relevance
“…We thus infected HFs with CHIKV at an MOI of 10 as described above. At 4,8,16, and 24 h postinfection, the cell culture media was replaced ("pulsed") with medium containing puromycin for 15 min and "chased" for 60 min with puromycin-free medium, after which whole-cell lysates were harvested and subjected to SDS-PAGE. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus infected HFs with CHIKV at an MOI of 10 as described above. At 4,8,16, and 24 h postinfection, the cell culture media was replaced ("pulsed") with medium containing puromycin for 15 min and "chased" for 60 min with puromycin-free medium, after which whole-cell lysates were harvested and subjected to SDS-PAGE. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HFs were grown on coverslips in 24-well plates and treated as described above. The cells were washed twice with PBS, fixed for 30 min in 3.7% formaldehyde, washed, and quenched for 10 min using 50 mM NH 4 Cl. Cells were permeabilized with 0.1% Triton X-100 for 7 min and washed three times with PBS containing 2% bovine serum albumin (BSA).…”
mentioning
confidence: 99%
“…27 Yet, MYXV productively infects cultured cancer cells from several species. 811 Although MYXV-encoded protein expression has been observed in noncancerous cells after intracranial injection of recombinant MYXV, protein expression is transient and no clinical disease is observed.…”
Section: Introductionmentioning
confidence: 99%
“…The host range determinants that mediate this cancer-specific tropism of MYXV outside the rabbit host are still being investigated, but at least two different intracellular pathways have been implicated in this cellular discrimination to date: (i) the failure of many cancer cells to induce an effective antiviral response, such as the synergistic interferon and tumor necrosis factor pathway that effectively aborts MYXV replication in primary nontransformed human cells (18,19), and (ii) the constitutive activation of Akt in many cancer cells that favors permissive virus replication (20,21). We have also recently shown that MYXV can selectively infect and kill primary human leukemic stem and progenitor cells while sparing normal human stem and progenitor cells derived from bone marrow in terms of differentiation potential in vitro and the ability to engraft recipient NOD/ scid/IL2 receptor gamma-chain knockout (NSG) mice in vivo (22).…”
mentioning
confidence: 99%